Patterns of Socio-Economic Relations in Gold Mining in Bombana Regency - Patunduk; Jamaluddin Hos; Ambo Upe (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
The purpose of this study was to determine the pattern of socio-economic relations in gold mining in Bombana Regency. This research was carried out in Tahi Ite Village, Rarowatu District, Bombana Regency by using a qualitative approach. The results showed that the pattern of socio-economic relations in gold mining in Tahi Ite Village, Rarowatu Subdistrict, Bombana District intertwined, among others; 1) Government's Social-Economic Relationship with the Community, namely the transfer of management with consideration of income. 2) Government's Socio-Economic Relations with Investors, namely increasing regional own-source revenue (PAD) through profit-sharing/royalty 3) Investor's Social-Economic Relationship with the Community, namely the opening of employment opportunities. 4) Socio-Economic Relations Among Communities, namely land management by way of profit sharing or percent of the land.